Quantum tempest - Cussler, Clive; Maden, Mike (Cussler, Clive. Oregon files adventures, 2025)
Juan Cabrillo and the crew of the Oregon face a ghost ship, deadly assassins and a threat from Cabrillo's own past in their race to stop the launch of the world's deadliest machine.